2016
DOI: 10.1038/srep31510
|View full text |Cite
|
Sign up to set email alerts
|

A magnetic synapse: multilevel spin-torque memristor with perpendicular anisotropy

Abstract: Memristors are non-volatile nano-resistors which resistance can be tuned by applied currents or voltages and set to a large number of levels. Thanks to these properties, memristors are ideal building blocks for a number of applications such as multilevel non-volatile memories and artificial nano-synapses, which are the focus of this work. A key point towards the development of large scale memristive neuromorphic hardware is to build these neural networks with a memristor technology compatible with the best can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
173
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 227 publications
(175 citation statements)
references
References 40 publications
1
173
0
1
Order By: Relevance
“…This dependence of resistance on the charge is the hallmark of memristor devices. Such memristive behavior has been demonstrated in magnetic tunnel junction with more than 15 intermediate resistance states [108]. Recently, it has also been shown that similar smooth magnetization variations can be triggered by spin-orbit torques in a magnetic stripe on top of an antiferromagnetic layer [109].…”
Section: Implementations Of Bioinspired Hardware Using Spintronicsmentioning
confidence: 98%
See 1 more Smart Citation
“…This dependence of resistance on the charge is the hallmark of memristor devices. Such memristive behavior has been demonstrated in magnetic tunnel junction with more than 15 intermediate resistance states [108]. Recently, it has also been shown that similar smooth magnetization variations can be triggered by spin-orbit torques in a magnetic stripe on top of an antiferromagnetic layer [109].…”
Section: Implementations Of Bioinspired Hardware Using Spintronicsmentioning
confidence: 98%
“…Spintronics offers many approaches for tuning the coupling between magnetic oscillators needed to generate the desired synchronization patterns. When the coupling is electrical, memristors can be inserted in the current lines connecting the oscillators [108]. When the coupling is induced by spin waves, it can be modified by spin-orbit torque locally damping or enhancing the wave amplitude.…”
Section: Implementations Of Bioinspired Hardware Using Spintronicsmentioning
confidence: 99%
“…Compared with RRAM, MRAM and PCM also have the advantage of technological maturity, while showing little difference in programming speed (∼ns) and operation voltage . However, despite some breakthroughs, MRAM and PCM show relatively poor analog switching behavior due to the low on/off ratio and the uncontrolled RESET, respectively. Multiterminal cells, such as FeFETs, ECRAM, and 3T1C + 2T2R (3‐transistor 1‐capacitor + 2‐transistor 2‐resistor), allow for more controllable and linear analog switching as a trade‐off for complexity, but their reliability requires more evaluation due to the complex cell structure and unclear working mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…In the last years, several ideas have been investigated. A first concept based on domain wall-based magnetic tunnel junctions (MTJs) was published in 2016 [4]. The resistance variation is achieved through displacement of a domain wall (DW) in the free layer of a perpendicular MTJ.…”
Section: Introductionmentioning
confidence: 99%